Combined Interhemispheric and Transsylvian Approach for Resection of Craniopharyngioma - Inoue, Tomohiro; Ono, Hideaki; Tamura, Akira; Saito, Isamu (Journal of Neurological Surgery Part B: Skull Base, 2018)
We present a 37-year-old male case of cystic suprasellar huge craniopharyngioma, who presented with significant memory disturbance due to obstructive hydrocephalus. Combined interhemispheric and pterional approach was chosen to resect huge suprasellar tumor. Interhemispheric trans-lamina terminalis approach was quite effective to resect third ventricular tumor, while pterional approach was useful to dissect tumor out of basilar perforators and stalk.The link to the video can be found at: https://youtu.be/BoYIPa96kdo.
Keywords: interhemispheric approach; lamina terminalis; pterional approach; craniopharyngioma